Influence of water matrix on the degradation of organic micropollutants by ozone based processes: A review on oxidant scavenging mechanism - Asghar, Anam; Lutze, Holger V.; Tuerk, Jochen; Schmidt, Torsten C. (Journal of hazardous materials, 2022)
The prevalence of organic micropollutants (OMPs) in aquatic environment has expedited scientific and regulatory efforts to retrofit existing wastewater treatment plants (WWTPs). The current strategy involves WWTPs upgrading with post-ozonation i.e., ozone (O3) and/or peroxone process (O3 +H2O2). Still, ozone-based degradation of OMPs faces several challenges. For example, the degradation mechanism and kinetics of OMPs could largely be affected by water matrix compounds which include inorganic ions and natural organic matter (NOM). pH also plays a decisive role in determining the reactivity of the oxidants (O3, H2O2, andHO•), stability and speciation of matrix constituents and OMPs and thus susceptibility of OMPs to the reactions with oxidants. There have been reviews discussing the impact of matrix components on the degradation of OMPs by advanced oxidation processes (AOPs). Nevertheless, a review focusing on scavenging mechanisms, formation of secondary oxidants and their scavenging effects with a particular focus on ozonation and peroxone process is lacking. Therefore, in order to broaden the knowledge on this subject, the database ‘Web of Science’ was searched for the studies related to the ‘matrix effect on the degradation of organic micropollutants by ozone based processes’ over the time period of 2004–2021. The relevant literature was thoroughly reviewed and following conclusions were made: i) chloride has inhibitory effects if it exits at higher concentrations or as free chlorine i.e. HOCl/ClO−. ii) The inhibitory effects of chloride, bromide, HOBr/OBr− and HOCl/ClO− are dominant in neutral and alkaline conditions and may result in the formation of secondary oxidants (e.g., chlorine atoms or free bromine), which in turn contribute to pollutant degradation or form undesired oxidation by-products such as BrO3–, ClO3– and halogenated organic products. ii) NOM may induce inhibitory or synergetic effects depending on the type, chemical properties and concentration of NOM. Therefore, more efforts are required to understand the importance of pH variation as well as the effects of water matrix on the reactivity of oxidants and subsequent degradation of OMPs. [Display omitted] •pH plays a deceive role in determining the reactivity of oxidants and speciation of MPs.•NOM may have promoting or inhibitory effects depending on the aromaticity of its structure.•Peroxone process has negligible effect on reducing the inhibitory effects of matrix components.